IMPLEMENTASI PEMBELAJARAN AL-QUR’AN MELALUI PROGRAM 3T-ULC (TAHFIDZ UMMI, TAHFIDZ LDS, DAN TAHFIDZ CAMP) DI SEKOLAH DASAR ISLAM AL-GHAFFAAR KECAMATAN DAU MALANG JAWA TIMUR - Wirdatul Istiqomah; Khoirul Asfiyak; Muhammad Sulistiono (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2020)
Researchers try to describe the results of research conducted by researchers relating to the Implementation of Al-Qur'an Learning through the 3T-ULC program. In learning the Qur'an the students are very enthusiastic, but the teacher has not been able to fully implement the Ummi method because of different individual abilities, and many teachers do not have Ummi certificates. These conditions can be overcome by the condition of the school environment that always accustoms children to read and memorize the Qur'an, so that these deficiencies can be overcome. The purpose of this study is to describe the conditions of learning the Qur'an 3T-ULC, supporting and inhibiting factors, as well as the strategies used in Al-Qur'an learning. This research uses a qualitative approach and type of case study research, so that it can see directly the conditions that occur in the field and can obtain a complete and accurate information in accordance with the object under study. Data analysis uses data collection, data condensation, data presentation and drawing conclusions. The results of this study are that in learning the Qur'an using the Ummi method it has not been fully implemented well, but the school continues to try to correct these deficiencies, so as to produce graduates who excel in the field of the Qur'an.